Strategi Penyelesaian Masalah Lingkungan Di Desa Pesouha Kecematan Pomala Kabupaten Kolaka - Nuraisyah Nuraisyah; Nurhidaya Nurhidaya; Astrid Octavira; Rasya Permata Ditya; Ketut Mahadi Agustayana; Dimas Octayanto; Ahmad Iskandar; Nasarudin Nasarudin (Geosfera: Jurnal Penelitian Geografi, 2025)
This study looks into the environmental problems facing Pesouha Village in the Pomalaa Subdistrict of Kolaka. The biggest issues seem to be flooding and pollution, impacting the water, air, and soil around the area. The goal here is to find out what's causing these problems and suggest practical solutions that follow the ideas of sustainable development. To do this, we used a qualitative approach, including observing the area, talking to the village head, and reviewing documents. The findings show that changes in land use, poor drainage systems, and unmanaged mining activities are major factors behind the environmental decline. This has led to seasonal flooding, contaminated rivers, dust pollution from mining, and less fertile soil. The study emphasizes that better land management, stricter waste controls, and increasing community awareness and involvement are key to tackling these issues. By adopting these steps, we hope to help create a healthier, more sustainable environment for Pesouha Village.